Analisis Bahasa Gaul Remaja dalam Film Into the Beat - Hasugian, Masni; Rina Evianty (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study examines youth slang (Jugendsprache) in the film Into the Beat (2020) through semantic and morphological approaches. The background of the research is based on the phenomenon of youth language development, which is dynamic, creative, and rich in socio-cultural meaning, yet often difficult for foreign speakers to understand. Youth language is chosen as the object of study because it reflects identity, group solidarity, and the communicative creativity of young people, and frequently appears in media, particularly films. The theoretical framework refers to experts’ perspectives on the characteristics of youth language, including the use of Anglicisms, abbreviations, metaphorization, and the formation of neologisms. The research method applied is descriptive qualitative, with data sources taken from the dialogues and subtitles of the film Into the Beat. The analysis is carried out based on Helmut Henne’s theory of youth language characteristics. The results reveal that youth slang in the film functions not only as a means of communication but also as a medium of emotional expression, lifestyle, and identity construction among German adolescents. Vocabulary such as alter, bro, krass, cool, and scheiße demonstrates creativity in morphological processes, including abbreviation, prefixation, and borrowing from foreign languages. The study concludes that youth slang plays an essential role in shaping characters, inter-character relationships, and the authenticity of the storyline. Furthermore, youth language reflects the evolving cultural and social dynamics of adolescents. This research is expected to contribute to linguistic studies, particularly semantics, and to serve as a valuable resource in German language learning by expanding vocabulary and fostering an understanding of authentic communication patterns among German teenagers.